2013
DOI: 10.1063/1.4809829
|View full text |Cite
|
Sign up to set email alerts
|

Giant enhancement in the magnetostrictive effect of FeGa alloys doped with low levels of terbium

Abstract: We present the effects of terbium additives upon the microstructure and magnetic properties of Fe83Ga17Tbx alloys (x = 0, 0.2, 0.4, 0.6, and 0.8), prepared by vacuum electric arc-melting and directional solidification techniques. Experiments indicate that small amounts of terbium more than double the saturation magnetostriction of a [110] textured Fe83Ga17 alloy with λ = 72 × 10−6 and lower the magnetostriction saturation field. The pronounced increase in magnetostriction stems from the appearance of [100] tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 12 publications
4
31
0
Order By: Relevance
“…Focusing on Tb-doped Fe-Ga alloys, Jiang et al reported the increase of magnetostriction from 72 ppm to 160 ppm in the directionally solidified Fe 83 Ga 17 Tb x (x = 0.2) polycrystalline alloys [9]. The increase of the magnetostriction was attributed to the formation of preferential orientation enhanced by the precipitation of Tb-rich phase [9].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Focusing on Tb-doped Fe-Ga alloys, Jiang et al reported the increase of magnetostriction from 72 ppm to 160 ppm in the directionally solidified Fe 83 Ga 17 Tb x (x = 0.2) polycrystalline alloys [9]. The increase of the magnetostriction was attributed to the formation of preferential orientation enhanced by the precipitation of Tb-rich phase [9].…”
Section: Introductionmentioning
confidence: 95%
“…The increase of the magnetostriction was attributed to the formation of preferential orientation enhanced by the precipitation of Tb-rich phase [9]. Further, in the [110]-textured Fe 81 Ga 19 Tb x (x = 0.3) polycrystalline alloy, Fitchorov et al found that Tb doping resulted in an increase in magnetization, a reduction of saturation field and a decrease in magnitude of the temperature coefficient of the mangetostriction [12].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Tb doping resulted in an increase in magnetization, a reduction of saturation field, as well as a decrease in magnitude of the magnetostriction temperature coefficient. Similarly, L.P. Jiang et al [15] indicated that the low-level doping of terbium can enhance the magnetostrictive coefficient of Fe-Ga alloy at room temperature. Moreover, L.P. Jiang et al [16] studied the microstructure and magnetostriction of Fe 83 Ga 17 Dy x (x=0, 0.2, 0.4, 0.6) alloys.…”
Section: Introductionmentioning
confidence: 96%
“…Another important application of orientation is in the magnetostrictive materials, which have drawn ever-increasing attention due to their wide applications in acoustic transducers, actuators, stress sensors and so on [6][7][8][9]. Actually, enhanced magnetostriction has been found in some textured alloys, such as Fe-Ga [10][11][12][13], Terfenol-D [14,15], Ni-Mn-Ga [16,17], and Ni-Mn-In [18,19]. However, there are still some drawbacks in current magnetostrictive materials, such as high-cost (Terfenol-D), limited magnetostriction value (Fe-Ga), or irreversibility (Ni-Mn-Ga and Ni-Mn-In), which have hindered their application to a large extent.…”
Section: Introductionmentioning
confidence: 99%